IMPROVING STUDENTS’ WRITING RECOUNT TEXT THROUGH WRITING DAIRY - MIMIN AMINAH (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN, 2018)
The research using classroom action research method, this research involved students in tenth grade at SMKN Cijambe. The research data obtained from tests for three cycles, and observation sheets. Furhermore the data was analyzed to determine the increase in students' ability of writing recount text and also the response of students towards teaching recount text by using writing dairy.The improvement appeared in the average of the score in the cycle I, Cycle II and cycle III. The average score in cycle I was 61,59 and it increased into 76,9 in cycle II. In the cycle III the average was 79,63. The students who passed Kriteria Ketuntasan Minimum (KKM) was 27% or it was 6 students in cycle I and it was 77% passing the KKM or it was 17 students passing the KKM in cycle II. In third cycle all students passed KKM with 100% or it was 22 students passing the KKM in cycle III. The minimum score in cycle I was 45 but it was 55 in cycle II. The minimum score was 75 in cycle III. The maximum score was 80 in cycle I and it was 85 in cycle II, finally 85 in cycle III. The results data analysis demonstrate that using writing dairy method can improve students' writing ability on recount text. The students’ also gave a good response. It demonstrate on observation sheet that filled out by the observer during three cycles.